2008
DOI: 10.1182/blood-2008-06-165803
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T lymphocytes mediate in vivo clearance of plasmid DNA vaccine antigen expression and potentiate CD8+ T-cell immune responses

Abstract: IntroductionPlasmid DNA vaccines are a promising modality for immunization against a variety of infectious agents because they are safe, readily scalable, and easy distributed. Plasmid DNA vaccine vectors can elicit CD8 ϩ cytotoxic T lymphocytes (CTLs), CD4 ϩ T helper cell immune responses, as well as humoral immune responses. Nonetheless, the utility of DNA immunogens has been limited by their failure to elicit sufficiently potent immune responses. 1 One potential explanation for the limited immunogenicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…2D). Together with earlier findings that DNA antigen clearance is ␤2m-independent (22), these findings suggest that the type II NKT mediate this function.…”
Section: Dna Vaccine Antigen Expression Damping Is Dependent On Nktsupporting
confidence: 64%
See 1 more Smart Citation
“…2D). Together with earlier findings that DNA antigen clearance is ␤2m-independent (22), these findings suggest that the type II NKT mediate this function.…”
Section: Dna Vaccine Antigen Expression Damping Is Dependent On Nktsupporting
confidence: 64%
“…Thus, the model seems to create an environment that favors the immune potentiating function, rather than the suppressive function of NKT cells. We have previously shown that these CD4 ϩ T cells clear plasmid DNA antigen expression though a MHC class II-restricted Fas/FasL-dependent mechanism, and that depletion of CD4 ϩ T cells leads to a reduction in the plasmid DNA antigen-specific CD8 ϩ T cell immune response (22). Therefore, the NKT-cell enhanced CD4 ϩ helper cells might also be responsible for the increase of the plasmid DNA antigen-specific CD8 ϩ T cell immune response.…”
Section: Discussionmentioning
confidence: 99%
“…We also know that Fas/FasL interactions reduce CD8 ϩ T-cell responses to plasmidencoded antigens by destroying the transfected antigenpresenting cell. 17,18 The superior ELISPOT responses in our study suggest that interfering with the Fas/FasL interaction protected these antigen-specific cells from destruction. Preservation of CCR5 ϩ CD4 T cells upon anti-FasL treatment did not result in any increase in viral replication.…”
Section: Discussionmentioning
confidence: 83%
“…Plasmid DNA immunization of mice triggered a response by class II-restricted CD4 ϩ T cells that expressed FasL and killed the transfected antigenpresenting cells. 17 When plasmid DNA immunizations were performed in Fas Ϫ/Ϫ mice 17 or class II Ϫ/Ϫ mice, 18 the damping of CD8 ϩ T-cell responses was not observed. The damping effect was independent of perforin expression and depended only on Fas/FasL interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of vaccine antigen expression in vivo in mice vaccinated i.m. with plasmid DNA is temporally correlated with local accumulation of T cells in the muscle and involves an apoptotic Fas/FasL-dependent process (8,10). Therefore, we coadministered plasmid DNA vaccine and plasmid DNAs encoding the antiapoptotic proteins BCL-xl, BCL-2, X-linked inhibitor of apoptosis protein (XIAP), or dominant negative (dn) mutants of caspase 9 (dnCasp9) and caspase 8 (dn-Casp8) to evaluate their abilities to augment the immunogenicity of a plasmid DNA immunogen.…”
Section: Resultsmentioning
confidence: 99%